An NMR Metabolomic Study on the Effect of Alendronate in Ovariectomized Mice - Chen, Shin-Yu; Yu, Hui-Tzu; Kao, Ju-Po; Yang, Chung-Chun; Chiang, Shen-Shih; Mishchuk, Darya O.; Mau, Jeng-Leun; Slupsky, Carolyn M. (PLOS ONE, 2014)
Alendronate sodium (Fosamax) is most widely used for the prevention and treatment of osteoporosis. It is a type of anti-resorptive agent that reduces the risk of fractures by changing bone turnover and bone mineral density. We investigated the effect of Fosamax on a mouse model of osteoporosis. Twenty-seven female C57BL/6JNarl mice were divided into three groups: sham, ovariectomized (OVX) and OVX + Fosamax (Fosamax). After 23 weeks, bone density of femurs was analyzed using microcomputed tomography (micro-CT), and serum was analyzed for osteoblast and osteoclast activity, as well as metabolites using nuclear magnetic resonance (NMR) spectroscopy. Fosamax increased bone mineral density and cortical bone thickness, and decreased osteoblast activity slightly. Fosamax did not significantly change osteoclast activity. Serum metabolomics revealed that Fosamax had profound effects on overall metabolism, as significantly higher concentrations of metabolites associated with energy metabolism (including TCA-cycle intermediates and glucose), 3-hydroxybutyrate, taurine, allantoin, acetate, and ethanol, as well as lower concentrations of aspartate were observed in the Fosamax-treated mice compared with the OVX mice. These results suggest that alendronate may work by increasing bone density through altered metabolic activity.